ChemInform Abstract: Synthesis of anti‐2, 3‐Dihydro‐1, 2, 3‐trisubstituted‐1H‐naphth‐[1, 2‐e][1, 3]oxazine Derivatives via Multicomponent Approach. Issue 44 (4th November 2014) - Borah, Ruli; Dutta, Arup Kumar; Sarma, Parishmita; Dutta, Champak; Sarma, Bipul
Abstract Electron‐poor amines are not applicable as starting material.